INCLUSION: CHALLENGES FOR EARLY CHILDHOOD EDUCATORS - Figueiredo, Celma Cynara de; Borges, Fátima Cristina Marinho Corrêa; Florentino, Magda de Almeida (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
This article reflects on the difficulties faced by educators of early childhood education, facing the challenge of including children with special educational needs in the day care space. The Law of Guidelines and Bases of National Education nº 9.394/96 determines that people with special needs, including those with disabilities, are included in classrooms and regular schools, including in institutions of early childhood education. However, the implementation of the Law comes up against numerous difficulties, since inclusion demands broad processes of pedagogical organization (integrated planning, selection of methodologies that meet the different needs, material and pedagogical time, among others). In order to know how the laws work and in the lived reality, we will examine and reflect on the main existing laws and documents.